Use of sulfite and hydrogen peroxide to control bacterial contamination in ethanol fermentation - Chang, IS; Kim, BH; Shin, PK (AMER SOC MICROBIOLOGY, 1997)
Lactic acid bacteria isolated from an industrial-scale ethanol fermentation process were used to evaluate sulfite as a bacterial-contamination control agent in a cell-recycled continuous ethanol fermentation process. The viabilities of bacteria were decreased by sulfite at concentrations of 100 to 400 mg liter(-1), while sulfite at the same concentrations did not change the viability of the Saccharomyces cerevisiae strain used in this process, Sulfite was effective only in the presence of oxygen. Bacteria showed differences in their susceptibilities to sulfite, Facultatively heterofermentative Lactobacillus casei 4-3 was more susceptible than was obligatory heterofermentative Lactobacillus fermentum 7-1. The former showed higher enzyme activities involved in the production and consumption of hydrogen peroxide than did the latter, The viability of L. fermentum 7-1 could be selectively controlled by hydrogen peroxide at concentrations of 1 to 10 mM. Based on these findings, it is hypothesized that the sulfur trioxide radical anions formed by peroxidase in the presence of hydrogen peroxide are responsible for the control of contaminating bacteria, Sulfite did not kill the yeast strain, which has catalase to degrade hydrogen peroxide, A cell recycled continuous ethanol fermentation process was run successfully with sulfite treatments.
Keywords: TRIOXIDE RADICAL-ANION; LACTIC-ACID BACTERIA; SULFUR-DIOXIDE; OXIDATION